THE PRONOUN: ITS TYPES, FUNCTIONS AND GRAMMATICAL CHARACTERISTICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines the structural and semantic diversity of pronouns, highlighting their significance in linguistic systems. It categorizes pronouns based on form (simple, compound, phrasal) and meaning (personal, possessive, demonstrative, etc.), showcasing their functional versatility. Additionally, the discussion delves into the grammatical categories of pronouns, such as person, number, gender, case, reflexivity, and definiteness, explaining their roles in syntactic and semantic structures. Theoretical frameworks, including transformational grammar and cognitive linguistics, are referenced to contextualize pronouns' significance in communication and cognition. The conclusions emphasize the importance of pronouns in achieving linguistic efficiency and coherence, offering insights into their universal and language-specific features.